Review of caesarean sections at full dilatation - Babre, Vijaya Monish; Bendre, Kirti Rajesh; Niyogi, Geeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To study indications of second stage caesarean section. To study intraoperative and postoperative complications. To review maternal and perinatal outcome. Methods: This retrospective study was conducted at a tertiary teaching Institute. All second stage caesarean sections performed between a period 2008 to 2012 were analysed in terms of duration of 2nd stage of labour, instrumentation attempted prior to caesarean section, indication of caesarean-section, Intraoperative complications, maternal and perinatal outcome. Results: During the study period 2760, caesarean sections were performed out of them 61 were 2nd stage caesarean section. Out of 61 Caeserean 14 were given prior instrumental trial, followed by 2nd stage caesarean section. Intraoperative complications were higher in terms of blood loss, primary PPH, extension of uterine incision, in one case bladder injury was noticed. Patwardhan method was used in 23% cases for delivery deeply engaged head. Atonic PPH was seen in 11.5% of patiants.3.3% of patients had extension of uterine incision. 54% baby’s required NICU care. Increased incidence of post-operative febrile illness and wound infection were noted. Conclusions: Caeseraen section in the 2nd stage of labour is associated with significantly increased maternal morbidity. Neonatal morbidity and mortality also increases. A proper judgement is required by a skilled obstetrician to take a decision for instrumental delivery or ceaseraen section at full cervical dilatation.